2020
DOI: 10.1088/2053-1591/ab7270
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thermoplastic starch on the properties of polypropylene/high density polyethylene blend reinforced by nano-clay

Abstract: Polypropylene (PP) and high density polyethylene (HDPE) was melt-blended in pairs at a constant of 80:20 (mm) compositions; this blend is prepared by one-step reactive extrusion in a single-screw extruder. The present study aims to investigate the effect of thermoplastic starch (TPS) on the properties of PP and HDPE blend. This later has been investigated in the absence and presence of maleic anhydride grafted polyethylene (PE-g-MA), and reinforced by nano-clay. All the blends/ nano-bio-composites were prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…Numerous studies have been conducted in search of sustainable and ecological alternatives to deal with the excessive production of plastic derived from fossil hydrocarbons [ 6 , 7 , 8 , 9 , 10 ]. The main objective is to find low-cost and biodegradable materials with good mechanical properties and high quality [ 11 ]. One of the alternatives is biopolymers manufactured from biomass or organic waste, which come from natural sources because they are abundantly available and inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been conducted in search of sustainable and ecological alternatives to deal with the excessive production of plastic derived from fossil hydrocarbons [ 6 , 7 , 8 , 9 , 10 ]. The main objective is to find low-cost and biodegradable materials with good mechanical properties and high quality [ 11 ]. One of the alternatives is biopolymers manufactured from biomass or organic waste, which come from natural sources because they are abundantly available and inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…[14] This drawback can be minimized by using an appropriate synthetic polymer matrix along with TPS to prepare a hybrid composite. [15][16][17][18] The development of a new type of hybrid polymer matrix by mixing both synthetic and natural polymer may lead to open a new avenue and thus widen the area of applications and brings a new dimension to the world of polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…Abundant studies have revealed that the incorporation of starch to low density polyethylene (LDPE) follows the common trend for filler effects on the polymer properties. Deterioration of mechanical properties of this blend is due to incompatibility between two phases (Chaoui et al, 2020;Hammache et al, 2020;Waryat et al, 2013). Several efforts have been done to enhance the compatibility and adhesion between two phases including treatment either starch or polyethylene.…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable polymers based on the use of natural and abundant polymers such as starch (Hammache et al, 2020;Yuan et al, 2010;Sae-Qui et al, 2010;Kahar et al, 2012a;Kahar et al, 2012b), cellulose (Beg et al, 2016), lignin and chitin are the most commonly used due to their desirable properties. These materials are relatively cheap, abundant, easily available and produced from renewable and natural resources (Yamak, 2016).…”
Section: Introductionmentioning
confidence: 99%